Candid advice for new faculty members : a guide to getting tenure and advancing your academic career - Gasman, Marybeth (Myers Education Press, 2021)
A how-to guide for graduate students, post-docs, and junior faculty across a variety of disciplines. Drawing upon the author's own extensive experience and that of colleagues, Marybeth Gasman provides a valuable tool for attaining tenure and for the things one should do to advance their academic career.